Sleep Endoscopy in the Evaluation of Pediatric Obstructive Sleep Apnea - Aaron C. Lin; Peter J. Koltai (International Journal of Pediatrics)
Pediatric obstructive sleep apnea (OSA) is not always resolved or improved with adenotonsillectomy. Persistent or complex cases of pediatric OSA may be due to sites of obstruction in the airway other than the tonsils and adenoids. Identifying these areas in the past has been problematic, and therefore, therapy for OSA in children who have failed adenotonsillectomy has often been unsatisfactory. Sleep endoscopy is a technique that can enable the surgeon to determine the level of obstruction in a sleeping child with OSA. With this knowledge, site-specific surgical therapy for persistent and complex pediatric OSA may be possible.